Micro minerals- their deficiency disorders and treatment: A review - Sharma, M C; Joshi, Chinmay; Kumar, Mahesh Kumar (The Indian Journal of Animal Sciences, 2005)
In animal nutrition minerals are considered essential as their deficiency or withdrawl causes some impairment of function or induces some abnormality, which can be presented or cured once the mineral is supplied. Deficiency, clinical manifestations, diagnosis, and prevention and control related to all the trace minerals have been discussed here.